Did The Global Financial Crisis Alter Cross-market Correlation? A Copula-GARCH Approach - ZAYATI, MONTASSAR; BEN MIM, SAMI (Bankers, Markets & Investors, 2020)
This paper uses a wide variety of copulas to study the correlation between the US market and a sample composed of nine developed and emerging markets over a 13 years period, including the subprime crisis. We try to analyze the markets behavior during high volatility periods and assess if the financial crisis led to a significant and durable change in the cross-market correlation patterns. Results offer strong evidence in favor of a contagion effect. Developed markets are those who registered the most important increases in cross-market correlations during high volatility periods. This may be attributed to their high degree of financial integration. However, cross-market correlation is weak for the whole sample period and decreased during the post-crisis period, implying that international diversification still offers interesting opportunities for investors. Moreover, diversification opportunities are not restricted to emerging markets but also concern developed markets.